Improving physiotherapy students’ anatomy learning experience and short‐term knowledge retention—an observational study in Malta - Cuschieri, Sarah; Narnaware, Yuwaraj (My University, 2023)
Anatomy is physiotherapy's foundation. However, undergraduate classroom learning and knowledge acquisition‐retention remain questionable. This study explored the possibility of improving this learning experience and evaluates the gross anatomy of abdomen and pelvis short‐term knowledge retention among first‐year physiotherapy students in Malta. The online Kahoot! game‐based quiz platform was used through an instructor‐designed best‐of‐four multiple‐choice questions. Correctly answered questions and Kahoot! scores generated by the platform were utilized to measure knowledge retention. Kahoot! sessions 1 and 3 shared similar attendance and response rate and were compared together. The Mann–Whitney U test was used to compare Kahoot! scores and Chi test for trend to compare correctly answered questions. Students' perceived learning experiences before and after the introduction of the Kahoot quizzes were gathered through Likert scores and analyzed using McNamar's chi‐square test. Overall, a significantly increased trend in correctly answered questions (χ2: 23.38, p‐value: <0.001) across the Kahoot! sessions were evident. Four questions out of 12 exhibited significant Kahoot! scores differences. Students reported better learning experiences following the initiation of Kahoot! (χ2: 5.1, p‐value: 0.02). Indeed, all students agreed that the use of the interactive quiz improved their anatomy short term knowledge retention. Introducing an online interactive quiz as part of the lecture program may be useful to improve the learning experience and anatomy knowledge retention among physiotherapy students.
Keywords: anatomy; knowledge retention; Malta; physiotherapist students